Comparative evaluation of sonohysterosalpingography (Sono HSG) to diagnostic laparo-hysteroscopy in infertility - Kashyap, Monika; Verma, Aruna; Gupta, Abhilasha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim was to study whether sonohysterosalpingography (sono HSG) can be used for tubal and uterine assessment in primary and secondary infertility instead of invasive methods like diagnostic largo-hysteroscopy (DLH). Methods: This was prospective interventional study. This study conducted at Obstetrics and gynecology Department, Lala Lajpat Rai Memorial Medical College Meerut, India in infertile women. Bilateral tubal patency and various uterine pathologies were first evaluated by sono HSG followed by DLH. The results were compared. Results: Sono HSG was found to be sensitive and highly specific in diagnosing tubal/uterine factors with a sensitivity of 86.6%/58.33% and specificity of 80%/97.22%. The positive and negative predictive values were 92%/93.33% and 66%/77.78%. Conclusions: Thus transvaginal sono HSG with its accuracy and safety, is a promising screening and diagnostic technique in the evaluation of tubal patency on an ambulatory basis. In the future, it can replace the hysterosalpingography.